MULTITYPE BRANCHING PROCESSES IN CONTINUOUS TIME AS MODELS OF CANCER - Vitanov, Kaloyan; Slavtchova-Bojkova, Maroussia (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2017)
A generalization of the results for two-type decomposable branching processes model in continuous time derived in [9] is obtained. More precisely, the system of integral equations for probability generating functions (p.g.f.) of the (n + 1)−type processes is obtained. Another important result is the recursive equations satisfied by the p.g.f. of the number of mutations. The results obtained are the base for further research of probabilities of extinction and estimation of the risk of cancer recurrence.